Maternal Stress/Distress, Hormonal Pathways and Spontaneous Preterm Birth. Issue 3 (4th March 2013) - Kramer, Michael S.; Lydon, John; Goulet, Lise; Kahn, Susan; Dahhou, Mourad; Platt, Robert W.; Sharma, Shakti; Meaney, Michael J.; Séguin, Louise
Abstract: Background: Although second‐trimester blood corticotrophin‐releasing hormone (CRH) levels are robustly associated with preterm birth, the findings with respect to cortisol have been inconsistent, as have been those relating stress hormones to measured stressors and maternal distress. Methods: We measured plasma CRH, adrenocorticotrophic hormone (ACTH), cortisol, cortisol‐binding globulin, oestradiol and progesterone at 24–26 weeks in a nested case–control study of 206 women who experienced spontaneous preterm birth and 442 term controls. We also related the hormonal levels to measures of environmental stressors, perceived stress and maternal distress (also assessed at 24–26 weeks) and to placental histopathology. Results: With the exception of an unexpectedly low oestradiol : progesterone ratio among cases (adjusted odds ratio = 0.5 [95% confidence interval 0.3, 0.8] for ratios above the median in controls), none of the hormonal measures was independently associated with spontaneous preterm birth; placental histopathological evidence of infection/inflammation, infarction or decidual vasculopathy; or measures of maternal stress or distress. CRH levels were positively associated with cortisol, but not with ACTH, whereas ACTH was also positively associated with cortisol. Conclusions: Our findings suggest an intact pituitary–adrenal axis and confirm the positive feedback effect of cortisol on (placental) CRH. Neither of these hormonal pathways, however, was strongly linked to maternal stress/distress or to the risk of spontaneous preterm birth.